Incidence, outcomes and guideline compliance of out-of-hospital maternal cardiac arrest resuscitations: A population-based cohort study. (November 2018) - Lipowicz, Alain A.; Cheskes, Sheldon; Gray, Sara H.; Jeejeebhoy, Farida; Lee, Janice; Scales, Damon C.; Zhan, Cathy; Morrison, Laurie J.; Nascimiento, Barto; Scales, Damon; Ko, Dennis; et al.
Abstract: Background: Incidence and survival rates after cardiac arrest among pregnant women are reported for in-hospital cardiac arrests; the incidence and outcomes of maternal out-of-hospital cardiac arrest (OHCA) are unknown. Current cardiopulmonary resuscitation guidelines contain recommendations specific to this population; compliance with these has not been investigated. Objective: To report maternal OHCA incidence, outcomes, and compliance with recommended treatment guidelines. Methods: A population-based cohort study of consecutive maternal OHCAs from 2010 to 2014. Census data of all women of childbearing age provided the comparison. Resuscitation performance was measured against the 2010 American Heart Association (AHA) Guidelines. Results: Six maternal OHCAs were identified among 1085 OHCAs occurring in females of child bearing age (15–49) years; Incidence 1.71 per 100, 000 pregnant women (95% CI 0.21 to 6.18) vs. 20.18 OHCAs per 100, 000 females of child bearing age (95% CI, 18 to 22.62) p < 0.0001. Survival to hospital discharge was 16.7% (95% CI 3.0, 56.4%) after maternal OHCA vs. 6.8% (95% CI 5.4, 8.4) p < 0.0001 after OHCA in all females of childbearing age, and neonatal survival was 33.3% (95% CI 9.7, 70%). CPR quality metric compliance averaged 83% (range 75% to 100%); compliance with pregnancy-specific resuscitation guidelines ranged from 0% (uterine displacement) to 100% (intravenous line insertion above diaphragm and prehospital maternal team activation). Conclusion: The incidence of maternal OHCA was 1.71:100, 000. Survival was higher after maternal OHCA than after OHCA of non-pregnant females of childbearing age. Pregnancy-specific guideline compliance was low suggesting a need for training and better documentation to improve outcomes in these rare events.